Urgensi dan Fungsi Hadis dalam Pendidikan Islam - Anshory, Muhammad Isa; Sayidah, Aminatus; Mustofa, Ahmad Al (Lembaga Yasin AlSys, 2025)
Hadith is one of the sources of Islamic law that plays a vital role in explaining and complementing the Qur'an. This article aims to examine the urgency and function of hadith in the context of Islamic education, especially in explaining values ​​that are not explicitly stated in the Qur'an. In addition, we will discuss how hadith can be used as a basis for educational methodology. This study uses a literature approach, by tracing various primary and secondary sources that discuss the role of hadith in education. The results of the study show that hadith functions as an explanation, complement, reinforcement, and limitation of the verses of the Qur'an, thus becoming an important foundation for the development of a comprehensive Islamic education system. Furthermore, the function of hadith which includes explaining the law, strengthening moral values, and compiling a learning methodology based on compassion, makes it still relevant in the context of modern education. The practical implication of this study is the importance of a deep understanding of hadith in designing an Islamic education curriculum that focuses on character building and spiritual development.